2020
DOI: 10.2196/20529
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Electronic Device Use During Family Time and Family Well-Being: Population-Based Cross-Sectional Study

Abstract: Background Electronic devices (eDevices) may have positive or negative influences on family communication and well-being depending on how they are used. Objective We examined eDevice use during family time and its association with the quality of family communication and well-being in Hong Kong Chinese adults. Methods In 2017, a probability-based 2-stage random sampling landline telephone survey collected dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Although benefits from screen use are possible for both parents and children, the American Academy of Pediatrics has called for the careful management of screen time-even suggesting setting up screen-free times [11]. There is also consensus among researchers and clinicians that screen-free zones or times could be beneficial within families-particularly around mealtimes and bedtimes-to promote time together as a family and richer, more frequent parent-child interactions (e.g., [11,12,[51][52][53]). Overall, various reviews and metaanalyses have revealed that interventions developed to reduce children's screen time have shown at least small, positive impacts on child screen time (e.g., [54][55][56]).…”
Section: Introductionmentioning
confidence: 99%
“…Although benefits from screen use are possible for both parents and children, the American Academy of Pediatrics has called for the careful management of screen time-even suggesting setting up screen-free times [11]. There is also consensus among researchers and clinicians that screen-free zones or times could be beneficial within families-particularly around mealtimes and bedtimes-to promote time together as a family and richer, more frequent parent-child interactions (e.g., [11,12,[51][52][53]). Overall, various reviews and metaanalyses have revealed that interventions developed to reduce children's screen time have shown at least small, positive impacts on child screen time (e.g., [54][55][56]).…”
Section: Introductionmentioning
confidence: 99%